How can I solve these differential equations by using the Extended Linearity Principle.

a) Find the general solution of the differential equation

dy/dt = -4 y+ 3e^(-t)

b) Solve the initial-value problem

dy/dt +3y = cos 2t, y(0) = -1

Printable View

- Apr 5th 2011, 07:05 AMhansbahiaExtended Linearity Principle
How can I solve these differential equations by using the Extended Linearity Principle.

a) Find the general solution of the differential equation

dy/dt = -4 y+ 3e^(-t)

b) Solve the initial-value problem

dy/dt +3y = cos 2t, y(0) = -1 - Apr 5th 2011, 07:51 AMAckbeet
Well, the Extended Linearity Principle says that you can solve the DE by adding together the homogeneous solution and any particular solution. So what's the homogeneous solution?